Group Communication Patterns of Universitas Terbuka Students’ Online Community on WhatsApp - Amelia Yeza Pradhipta; Isma Dwi Fiani (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
This qualitative constructivist research focuses on understanding the group communication patterns that emerged from interaction within distance learning student’s online community. Although distance learning has allowed students to pursue higher education without being bound by time and space constraints, this learning mode also separates students from one another. Communication technology, such as the instant messaging platform WhatsApp, becomes an option for students to replace in-person interaction with virtual interaction. This research uses DeVito’s concept of group communication patterns to analyze the communication between students as a member of an online community on WhatsApp group chat. Based on the online observation data and interviews, this research has found that two group communication patterns emerged from the online community interaction: wheel pattern communication and star pattern communication. The patterns themselves depend on the conversation topic between group members. Wheel pattern typically emerges in a Q&A type of conversation where one member would ask questions and receive responses from multiple group members. Meanwhile, star pattern communication is found only in conversations related to sharing personal experiences as distance learning students.